(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Gridhrasi is one among the eighty Nanatmaja vatavyadhi described in the Ayurvedic text. In today’s era the changing lifestyle shifting duties, inappropriate posture, excessive two-wheeler travelling, irregular dietary habits, no exercise, these factors produce stress on spine and responsible for diseases like Gridhrasi. The cardinal signs and symptoms of Gridhrasi are Ruk, Toda, Spandhana in Sphik, Kati, Uru, Janu, Jhanga, and Pada in order Sakthikshep Nigraha which all these can be corelated to sciatica in the contemporary science. Sciatica is a painful condition that causes pain in the lower back radiating to lower limbs resulting from irritation of the sciatic nerve roots. The nerve extends from the lower back down each leg and when effected can cause severe discomfort varying from mild ache to sharp burning sensation even excruciating pain. It is more among the people of age between 30yrs and 50yrs. Panchakarma therapy is a unique potent approach of Ayurveda which attacks the very root cause of the disease cleanses the microcirculatory channels, removes the vitiated doshas and produces long lasting benefits. A female patient of age 53yrs approached our hospital with the history of pain in the lower back since 10 days radiating to bilateral lower limbs with the features of Gridhrasi that is sciatica, like pain, electric shock like sensation, stiffness, and burning sensation, difficulty in sitting, standing and walking for even for 5 minutes. Treatment plan included Abyanga, Choorna Pinda Sweda, Panchatiktha Ksheera Basthi, Prustabasthi, with Vasa Bala Ashwagandha Taila, along with Shamana Chikithsa. After 40 days of treatment patients’ symptoms were assessed and outcome as good. The patient who was finding difficulty in standing for 5 minutes found remarkable improvement in the signs and symptoms and also in general quality of the life.